Insights into post-emplacement lava flow dynamics at Mt. Etna volcano from 2016 to 2021 by synthetic aperture radar and multispectral satellite data - Beccaro, Lisa; Albano, Matteo; Tolomei, Cristiano; Spinetti, Claudia; Pezzo, Giuseppe; Palano, Mimmo; Chiarabba, Claudio (Frontiers in Earth Science, 2023)
Post-emplacement dynamics of lava flows is governed by several factors such as poroelastic deformation of the substrate; gravity-induced repacking and rearrangement of the vesicle-bearing fluid lava and other void spaces by superposed flows; lava densification processes; viscoelastic strain relaxation of the ground caused by the lava load; thermal cooling and contraction of the solid lava; and discrete motion of surface blocks. Here we investigate post-emplacement lava flow dynamics at the Mt. Etna volcano, and we infer on the possible causes by exploiting optical and radar satellite data. Synthetic aperture radar data from Sentinel-1 satellite mission provided high-resolution horizontal and vertical displacement rates and displacement time series of the lava flows emplaced on the Mt. Etna volcano summit from January 2016 to July 2021. Sentinel-2 multispectral data allowed to identify the lava flows boundaries emplaced during the December 2018 and May 2019 paroxysms. Finally, high resolution COSMO-SkyMed radar data allowed to account for the topographic changes generated by the lava emplacement by means of stereo radargrammetry technique. Such an unprecedented dataset provided a full picture of the lava flow dynamics, whose kinematics is governed lava cooling, which in turn produce thermal contraction of the lava body and viscous compaction of the underlying substrate. Both phenomena act at different periods, being the thermal contraction predominant for recent lava flows. Downslope sliding is also invoked, especially for recent lava flows emplaced on high slope areas.